Method for improving selectivity of carbon dioxide electroreduction product by using Arabic gum solution as binder
By using gum arabic solution as a catalyst binder, the problems of high cost of copper nanocatalyst binder and low carbon dioxide retention are solved, and low cost, high activity and high selectivity carbon dioxide electroreduction technology is achieved, especially in ethylene , excellent performance in the production of ethane.
Patent Information
- Application Number
- CN202411361055.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-20
AI Technical Summary
The existing copper nanocatalyst binders are expensive, and the carbon dioxide retention in the H-type electrolytic cell is low, which limits the cost saving and catalytic activity of carbon dioxide electroreduction technology.
Using a cheap and easy-to-get gum arabic solution as the catalyst binder, uniform copper ink and carbon black ink are formed by sonication, sprayed onto the gas diffusion electrode, forming a Cu/C composite cathode catalyst, and carried out in an H-type electrolytic cell. Constant potential electrolysis improves the selectivity of carbon dioxide electroreduction products.
The cost is significantly reduced, the catalytic reaction activity and the selectivity of dicarbon alkane products are improved, especially the formation of ethylene and ethane, and the gas retention performance of gum acacia is conducive to the transport of carbon dioxide and the reaction participation of the catalyst surface.
Smart Images

Figure CN119162611A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrochemical carbon dioxide catalytic reduction, and specifically relates to a method for improving reaction activity and dicarbon alkane selectivity by using cheap and readily available hydrophilic gum arabic solution instead of expensive Nafion reagent as a catalyst binder. Background Art
[0002] Over the past century, excessive carbon dioxide has been released into the atmosphere due to the consumption of fossil fuels, causing climate change and other environmental problems. Electrochemical carbon dioxide reduction reactions achieved by renewable energy sources such as solar and wind energy are considered to be a promising strategy to address these problems. Sequester the emitted carbon dioxide into chemical feedstocks and reduce the use of fossil fuels in the chemical production industry. Carbon-2 reduction products, such as ethylene, ethane, and ethanol, are more favored due to their higher energy density and broader market size. Copper-based catalysts are considered to be the only metal-based catalysts that can catalyze carbon-carbon coupling to synthesize carbon-2 products due to their appropriate binding energy to the reduction intermediates. However, pure metallic copper nanoparticles have low catalytic activity and poor selectivity for carbon-2 products. More and more strategies such as material synthesis and microenvironment regulation are used to improve the catalytic efficiency of pure copper metal, but the cost is relatively high.
[0003] The H-type electrolytic cell is the most classic electrolytic cell for carbon dioxide electroreduction, with the advantages of easy assembly and simple operation. In the cathode chamber, the carbon dioxide required for the reaction must first be dissolved in the electrolyte, and then diffuse to the catalyst surface to participate in the reduction reaction. However, due to the low solubility of carbon dioxide in aqueous solution, the current density of the H-type electrolytic cell is far lower than the index requirements for industrial applications. Improving the retention of carbon dioxide in the electrolyte can increase the concentration of raw materials participating in the reaction on the catalyst surface.
[0004] Nafion is a perfluorosulfonic acid ion exchange resin. Due to its good proton conductivity, it is a general binder choice used to bind catalyst powder to gas diffusion electrodes. However, the complex polymerization, sulfonation and other synthesis processes make its market price very high, which to a certain extent restricts the cost saving of carbon dioxide electroreduction technology. Therefore, finding more economical alternative materials to achieve similar performance is the key to the future development of electrocatalytic carbon dioxide technology. Gum Arabic is a natural plant gum polysaccharide. It is a macromolecule composed of many monosaccharide molecules connected by glycosidic bonds. It can form a stable colloidal solution in water to produce viscosity and maintain structural stability in a wide range of potential windows. In addition, gum Arabic is an important carbon dioxide stabilizer in carbonated beverages, which can help maintain bubbles and uniform distribution in the liquid. Therefore, it is meaningful to develop a hydrophilic gum Arabic solution to replace the expensive Nafion as a binder for carbon dioxide electroreduction catalysts to improve reaction activity and selectivity of carbon dioxide products. Summary of the invention
[0005] The purpose of the present invention is to solve the problems of high cost of existing copper nanocatalyst binders and low carbon dioxide retention in H-type electrolytic cells, and to provide a method for using a low-cost and simple-to-prepare gum arabic solution as a catalyst binder, while improving the catalytic reaction activity and the selectivity of the dicarbon product alkane.
[0006] The method of the present invention using gum arabic solution as a binder to improve the selectivity of carbon dioxide electroreduction products is achieved by the following steps:
[0007] Step 1, dissolving gum arabic powder in deionized water to obtain a gum arabic solution;
[0008] Step 2: adding copper nanoparticles, dispersant isopropanol and oscillating glass beads into a centrifuge tube and then performing ultrasonic treatment, then adding gum arabic solution and performing ultrasonic treatment again to form a uniform copper ink;
[0009] Step 3, adding conductive carbon black, dispersant methanol and oscillating glass beads into a centrifuge tube and then performing ultrasonic treatment, then adding gum arabic solution and performing ultrasonic treatment again to form a uniform carbon black ink;
[0010] Step 4: first spray copper ink onto the gas diffusion electrode, and then spray carbon black ink onto the gas diffusion electrode to obtain a Cu / C composite cathode catalyst;
[0011] Step 5: Load the Cu / C composite cathode catalyst into an electrolytic cell, continuously introduce carbon dioxide into the electrolytic cell, perform constant potential electrolysis using a KHCO3 solution as an electrolyte, and collect carbon dioxide electro-reduction products, thereby completing a method for improving the selectivity of carbon dioxide electro-reduction products using an arabic gum solution as a binder.
[0012] The method of using gum arabic solution as a binder to improve the selectivity of carbon dioxide electroreduction products includes the following beneficial effects:
[0013] 1. The present invention uses a cheap and readily available gum arabic solution as a binder for the catalyst. This substitution can significantly reduce costs, which is particularly important for large-scale implementation of carbon dioxide reduction technology and helps to improve the economic feasibility of the entire process.
[0014] 2. The present invention uses an Arabic gum solution with excellent viscosity and stability as a binder for the catalyst, so that the composite layer of nano-copper and conductive carbon black is tightly bound to the gas diffusion electrode, and the structure of the Arabic gum does not change during the reduction process.
[0015] 3. The unique gas retention properties of gum arabic provide a microscopic environment that is favorable for the transmission of carbon dioxide in the electrolyte, which is conducive to diffusion to the catalyst surface to participate in the reduction reaction. In addition, the moderate hydrophilicity of gum arabic increases the formation of alkane products, especially dicarbon products such as ethylene and ethane. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 It is an LSV curve diagram of Example 1 and Comparative Example 1, a gum arabic solution with a mass concentration of 5% and a Nafion with a copper loading of 1 mg and a conductive carbon black loading of 1 mg;
[0017] Figure 2 It is an LSV curve diagram of Example 2 and Comparative Example 2, where the mass concentration of 5% gum arabic solution and 5% Nafion are 2 mg of copper loading and 1 mg of conductive carbon black loading;
[0018] Figure 3 It is an LSV curve diagram of Example 3 and Comparative Example 3, a gum arabic solution with a mass concentration of 5% and a Nafion with a copper loading of 3 mg and a conductive carbon black loading of 1 mg;
[0019] Figure 4 It is an LSV curve diagram of Example 4 and Comparative Example 4, a gum arabic solution with a mass concentration of 5% and a Nafion with a copper loading of 4 mg and a conductive carbon black loading of 1 mg;
[0020] Figure 5 is an LSV curve diagram of Example 5, Example 3, Example 6 and Example 7 when the mass concentration of the gum arabic solution is 2%, 5%, 10% and 15%;
[0021] Figure 6 It is the Faraday efficiency diagram of the di-carbon alkane product of Example 8 and Comparative Example 5 at five different potentials. DETAILED DESCRIPTION
[0022] Specific implementation method 1: The method of using gum arabic solution as a binder to improve the selectivity of carbon dioxide electroreduction products is implemented according to the following steps:
[0023] Step 1, dissolving gum arabic powder in deionized water to obtain a gum arabic solution;
[0024] Step 2: adding copper nanoparticles, dispersant isopropanol and oscillating glass beads into a centrifuge tube and then performing ultrasonic treatment, then adding gum arabic solution and performing ultrasonic treatment again to form a uniform copper ink;
[0025] Step 3, adding conductive carbon black, dispersant methanol and oscillating glass beads into a centrifuge tube and then performing ultrasonic treatment, then adding gum arabic solution and performing ultrasonic treatment again to form a uniform carbon black ink;
[0026] Step 4: first spray copper ink onto the gas diffusion electrode, and then spray carbon black ink onto the gas diffusion electrode to obtain a Cu / C composite cathode catalyst;
[0027] Step 5: Load the Cu / C composite cathode catalyst into an electrolytic cell, continuously introduce carbon dioxide into the electrolytic cell, perform constant potential electrolysis using a KHCO3 solution as an electrolyte, and collect carbon dioxide electro-reduction products, thereby completing a method for improving the selectivity of carbon dioxide electro-reduction products using an arabic gum solution as a binder.
[0028] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the mass concentration of the gum arabic solution in step 1 is 5%-20%.
[0029] Specific implementation method three: This implementation method is different from specific implementation methods one or two in that the particle size of the copper nanoparticles in step two is 10-30 nm.
[0030] Specific embodiment 4: This embodiment is different from specific embodiments 1 to 3 in that in step 2, 5-10 mg of copper nanoparticles, 1.5-2.0 mL of dispersant isopropanol and oscillating glass beads are added to the centrifuge tube and then ultrasonically treated for 20-40 minutes, and then 50-100 μL of gum arabic solution is added and ultrasonically treated again for 20-40 minutes.
[0031] Specific implementation mode 5: This implementation mode is different from any one of specific implementation modes 1 to 4 in that the model of the conductive carbon black in step 2 is Vulcan XC-72.
[0032] Specific embodiment 6: This embodiment is different from any one of specific embodiments 1 to 5 in that in step 3, 2-5 mg of conductive carbon black, 1.5-2.5 mL of dispersant methanol and oscillating glass beads are added to the centrifuge tube and then ultrasonically treated, and then 20-50 μL of gum arabic solution is added and ultrasonically treated again.
[0033] Specific implementation method 7: The difference between this implementation method and one of specific implementation methods 1 to 6 is that the time of the two ultrasonic treatments in step 3 is 30 minutes.
[0034] Specific embodiment 8: This embodiment is different from specific embodiments 1 to 7 in that the loading amount of copper nanoparticles on the Cu / C composite cathode catalyst in step 4 is 1-5 mg·cm -2 , the loading amount of conductive carbon black is 0.5-1.5 mg·cm -2 .
[0035] The preferred loading amount of copper nanoparticles on the Cu / C composite cathode catalyst of this embodiment is 3-5 mg·cm -2 .
[0036] Specific implementation method 9: This implementation method is different from specific implementation methods 1 to 8 in that the electrolytic cell described in step 5 is an H-type electrolytic cell.
[0037] Specific embodiment ten: This embodiment differs from any one of specific embodiments one to nine in that the concentration of the KHCO3 solution in step five is 0.1 mol / L.
[0038] Example 1: The method of using gum arabic solution as a binder to improve the selectivity of carbon dioxide electroreduction products is implemented according to the following steps:
[0039] Step 1: Take 95g of deionized water and heat it to 60°C in a water bath, then add 5g of gum arabic powder, stir with a glass rod until it is completely dissolved, cool to 25°C at room temperature, and adjust the mass of the solution to 100g after cooling; filter with a 0.22μm filter element to obtain a 5% gum arabic solution, and store it in a centrifuge tube and seal it;
[0040] Step 2: Add 10 mg of copper nanoparticles with a particle size of 10-30 nm, 1.8 mL of dispersant isopropanol and 3 3 mm oscillating glass beads into a centrifuge tube and perform ultrasonic treatment for 30 minutes, then add 50 μL of 5% gum arabic solution and perform ultrasonic treatment again for 30 minutes to form a uniform copper ink;
[0041] Step 3: Add 5 mg of conductive carbon black, 2 mL of dispersant methanol and 3 3 mm oscillating glass beads to a centrifuge tube and perform ultrasonic treatment for 30 minutes, then add 20 μL of 5% gum arabic solution and perform ultrasonic treatment again for 30 minutes to form a uniform carbon black ink;
[0042] Step 4: First, spray the copper ink onto a working area of 1 cm 2 The gas diffusion electrode is then coated with carbon black ink to obtain a Cu / C composite cathode catalyst. The loading amount of copper nanoparticles on the Cu / C composite cathode catalyst is 1 mg cm -2 , the loading amount of conductive carbon black is 1.0 mg cm -2 .
[0043] Example 2: The difference between this example and Example 1 is that the loading amount of copper nanoparticles on the Cu / C composite cathode catalyst in step 4 is 2 mg·cm -2 , the loading amount of conductive carbon black is 1.0 mg cm -2 .
[0044] Example 3: The difference between this example and Example 1 is that the loading amount of copper nanoparticles on the Cu / C composite cathode catalyst in step 4 is 3 mg·cm -2 , the loading amount of conductive carbon black is 1.0 mg cm -2 .
[0045] Example 4: The difference between this example and Example 1 is that the loading amount of copper nanoparticles on the Cu / C composite cathode catalyst in step 4 is 4 mg·cm -2 , the loading amount of conductive carbon black is 1.0 mg cm -2 .
[0046] Example 5: The method of using gum arabic solution as a binder to improve the selectivity of carbon dioxide electroreduction products is implemented according to the following steps:
[0047] Step 1: Take 98g of deionized water and heat it to 60°C in a water bath, then add 2g of gum arabic powder, stir with a glass rod until it is completely dissolved, cool to 25°C at room temperature, and adjust the mass of the solution to 100g after cooling; filter with a 0.22μm filter element to obtain a gum arabic solution with a mass concentration of 2%, and store it in a centrifuge tube and seal it;
[0048] Step 2: Add 10 mg of copper nanoparticles with a particle size of 10-30 nm, 1.8 mL of dispersant isopropanol and 3 3 mm oscillating glass beads into a centrifuge tube and perform ultrasonic treatment for 30 minutes, then add 50 μL of 2% gum arabic solution and perform ultrasonic treatment again for 30 minutes to form a uniform copper ink;
[0049] Step 3: Add 5 mg of conductive carbon black, 2 mL of dispersant methanol and 3 3 mm oscillating glass beads to a centrifuge tube and perform ultrasonic treatment for 30 minutes, then add 20 μL of 2% gum arabic solution and perform ultrasonic treatment again for 30 minutes to form a uniform carbon black ink;
[0050] Step 4: First, spray the copper ink onto an area of 1 cm 2 The gas diffusion electrode is then coated with carbon black ink to obtain a Cu / C composite cathode catalyst. The loading amount of copper nanoparticles on the Cu / C composite cathode catalyst is 3 mg cm -2 , the loading amount of conductive carbon black is 1.0 mg cm -2 .
[0051] Example 6: The method of using gum arabic solution as a binder to improve the selectivity of carbon dioxide electroreduction products is implemented according to the following steps:
[0052] Step 1: Take 90g of deionized water and heat it to 60°C in a water bath, then add 10g of gum arabic powder, stir with a glass rod until it is completely dissolved, cool to 25°C at room temperature, and adjust the mass of the solution to 100g after cooling; filter with a 0.22μm filter element to obtain a gum arabic solution with a mass concentration of 10%, and store it in a centrifuge tube and seal it;
[0053] Step 2: Add 10 mg of copper nanoparticles with a particle size of 10-30 nm, 1.8 mL of dispersant isopropanol and 3 3 mm oscillating glass beads into a centrifuge tube and perform ultrasonic treatment for 30 minutes, then add 50 μL of 10% gum arabic solution and perform ultrasonic treatment again for 30 minutes to form a uniform copper ink;
[0054] Step 3, add 5 mg of conductive carbon black, 2 mL of dispersant methanol and 3 3 mm oscillating glass beads into a centrifuge tube and perform ultrasonic treatment for 30 minutes, then add 20 μL of 10% gum arabic solution and perform ultrasonic treatment again for 30 minutes to form a uniform carbon black ink;
[0055] Step 4: First, spray the copper ink onto an area of 1 cm 2 The gas diffusion electrode is then coated with carbon black ink to obtain a Cu / C composite cathode catalyst. The loading amount of copper nanoparticles on the Cu / C composite cathode catalyst is 3 mg cm -2 , the loading amount of conductive carbon black is 1.0 mg cm -2 .
[0056] Example 7: The method of using gum arabic solution as a binder to improve the selectivity of carbon dioxide electroreduction products is implemented according to the following steps:
[0057] Step 1: Take 85g of deionized water and heat it to 60°C in a water bath, then add 15g of gum arabic powder, stir with a glass rod until it is completely dissolved, cool to 25°C at room temperature, and adjust the mass of the solution to 100g after cooling; filter with a 0.22μm filter element to obtain a gum arabic solution with a mass concentration of 15%, and store it in a centrifuge tube and seal it;
[0058] Step 2: Add 10 mg of copper nanoparticles with a particle size of 10-30 nm, 1.8 mL of dispersant isopropanol and 3 3 mm oscillating glass beads to a centrifuge tube and perform ultrasonic treatment for 30 minutes, then add 50 μL of 15% mass concentration of gum arabic solution and perform ultrasonic treatment again for 30 minutes to form a uniform copper ink;
[0059] Step 3: Add 5 mg of conductive carbon black, 2 mL of dispersant methanol and 3 3 mm oscillating glass beads to a centrifuge tube and perform ultrasonic treatment for 30 minutes, then add 20 μL of 15% gum arabic solution and perform ultrasonic treatment again for 30 minutes to form a uniform carbon black ink;
[0060] Step 4: First, spray the copper ink onto an area of 1 cm 2 The gas diffusion electrode is then coated with carbon black ink to obtain a Cu / C composite cathode catalyst. The loading amount of copper nanoparticles on the Cu / C composite cathode catalyst is 3 mg cm -2 , the loading amount of conductive carbon black is 1.0 mg cm -2 .
[0061] Embodiment 8:
[0062] During the preparation of copper ink and carbon black ink, a 5% gum arabic solution was added, and 1 cm 2 The gas diffusion electrode is sprayed with 3 mg of nano copper particles and 1 mg of conductive carbon black (i.e., the Cu / C composite cathode prepared in Example 3). Figure 3 , select potentials of -1.0, -1.2, -1.4, -1.6 and -1.8 V vs. RHE, and perform constant potential electrolysis respectively. The electrolytic cell is a H-type electrolytic cell from Gaoshi Ruilian, the cathode and anode electrolytes are both 0.1M KHCO3 solution, the electrolyte volume is 35mL, the proton exchange membrane is Nafion117, the reference electrode is a silver / silver chloride reference electrode, and the counter electrode is a platinum sheet. Before constant potential electrolysis, argon gas is introduced for 30 minutes to create an inert environment, and then carbon dioxide is introduced for 30 minutes until saturated. And at 10mL min -1Carbon dioxide was continuously introduced at a flow rate of , and electrolysis was performed at different potentials for 30 min. The products were collected by gas bags and analyzed by gas chromatography. The Faraday efficiency was calculated based on the product peak areas of ethylene and ethane. The results are as follows: Figure 6 .
[0063] Comparative Example 1:
[0064] The difference between Comparative Example 1 and Example 1 is that a Nafion solution with a mass concentration of 5% is used to replace the gum arabic solution.
[0065] Comparative Example 2:
[0066] The difference between Comparative Example 2 and Example 2 is that a Nafion solution with a mass concentration of 5% is used to replace the gum arabic solution.
[0067] Comparative Example 3:
[0068] The difference between Comparative Example 3 and Example 3 is that a Nafion solution with a mass concentration of 5% is used to replace the gum arabic solution.
[0069] Comparative Example 4:
[0070] The difference between Comparative Example 4 and Example 4 is that a Nafion solution with a mass concentration of 5% is used to replace the gum arabic solution.
[0071] Comparative Example 5:
[0072] The difference between Comparative Example 5 and Example 8 is that a Nafion solution with a mass concentration of 5% is used to replace the gum arabic solution.
[0073] Result analysis: Figure 1-4 It can be seen that only the current density of Nafion with a copper loading of 1 mg is higher than that of 5% gum arabic solution, while the current density of the other 5% gum arabic solutions is higher and the catalytic activity is better. Among them, the current density of Nafion with a copper loading of 2 mg and 3 mg is the best, reaching 40 mA cm -2 However, at a current density of -10 mA·cm -2 When the copper loading is 2 mg, the potential is -1.07388 V vs. RHE, while the potential is -1.05331 V vs. RHE when the copper loading is 3 mg, which is about 20 mV lower. This means that when the copper loading is 3 mg, the energy barrier of the carbon dioxide reduction reaction is reduced, making the electron transfer reaction easier to occur.
[0074] Depend on Figure 5 It can be seen that when the copper loading is controlled to be 3 mg, the current density of the 5% and 10% gum arabic solutions is about 40 mA cm -2 , while the current density of 2% and 15% gum arabic solution was only about 24 mA cm-2 and 29 mA cm -2 .Depend on Figure 6 It can be seen that at these five potentials, the overall Faraday efficiency of ethylene and ethane presents a volcano-type, which is consistent with many studies. Moreover, at these five potentials, the Faraday efficiency of gum arabic as a catalyst binder is higher than that of Nafion, which means that the hydrophilic gum arabic binder may affect the microenvironment of the catalyst surface, promote the combination of protons and carbon-carbon coupling structures, and further improve the product selectivity of dicarbon alkanes.
[0075] Finally, it should be noted that although the specific embodiments of the present invention have been described in detail, they should not be understood as limiting the scope of protection of this patent. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for improving the selectivity of carbon dioxide electroreduction products using a gum arabic solution as a binder, characterized in that The method for improving the selectivity of carbon dioxide electroreduction products by using gum arabic solution as a binder is implemented by the following steps: Step 1, dissolving gum arabic powder in deionized water to obtain a gum arabic solution; Step 2: adding copper nanoparticles, dispersant isopropanol and oscillating glass beads into a centrifuge tube and then performing ultrasonic treatment, then adding gum arabic solution and performing ultrasonic treatment again to form a uniform copper ink; Step 3, adding conductive carbon black, dispersant methanol and oscillating glass beads into a centrifuge tube and then performing ultrasonic treatment, then adding gum arabic solution and performing ultrasonic treatment again to form a uniform carbon black ink; Step 4: first spray copper ink onto the gas diffusion electrode, and then spray carbon black ink onto the gas diffusion electrode to obtain a Cu / C composite cathode catalyst; Step 5: Load the Cu / C composite cathode catalyst into an electrolytic cell, continuously introduce carbon dioxide into the electrolytic cell, perform constant potential electrolysis using a KHCO3 solution as an electrolyte, and collect carbon dioxide electro-reduction products, thereby completing a method for improving the selectivity of carbon dioxide electro-reduction products using an arabic gum solution as a binder.
2. The method for improving the selectivity of carbon dioxide electroreduction products using a gum arabic solution as a binder according to claim 1, characterized in that The mass concentration of the gum arabic solution in step 1 is 5%-20%.
3. The method for improving the selectivity of carbon dioxide electroreduction products using a gum arabic solution as a binder according to claim 1, characterized in that The particle size of the copper nanoparticles in step 2 is 10-30 nm.
4. The method for improving the selectivity of carbon dioxide electroreduction products using gum arabic solution as a binder according to claim 1, characterized in that In step 2, 5-10 mg of copper nanoparticles, 1.5-2.0 mL of dispersant isopropanol and oscillating glass beads are added to the centrifuge tube and then ultrasonically treated for 20-40 min, and then 50-100 μL of gum arabic solution is added and ultrasonically treated again for 20-40 min.
5. The method for improving the selectivity of carbon dioxide electroreduction products using gum arabic solution as a binder according to claim 1, characterized in that The model of the conductive carbon black in step 2 is Vulcan XC-72.
6. The method for improving the selectivity of carbon dioxide electroreduction products using gum arabic solution as a binder according to claim 1, characterized in that In step 3, 2-5 mg of conductive carbon black, 1.5-2.5 mL of dispersant methanol and oscillating glass beads are added to the centrifuge tube and then ultrasonically treated. Then, 20-50 μL of gum arabic solution is added and ultrasonically treated again.
7. The method for improving the selectivity of carbon dioxide electroreduction products using gum arabic solution as a binder according to claim 6, characterized in that The duration of the two ultrasonic treatments in step 3 is 30 min.
8. The method for improving the selectivity of carbon dioxide electroreduction products using gum arabic solution as a binder according to claim 1, characterized in that The loading amount of copper nanoparticles on the Cu / C composite cathode catalyst in step 4 is 1-5 mg cm -2 , the loading amount of conductive carbon black is 0.5-1.5 mg·cm -2 .
9. The method for improving the selectivity of carbon dioxide electroreduction products using gum arabic solution as a binder according to claim 1, characterized in that The electrolytic cell described in step 5 is an H-type electrolytic cell.
10. The method of claim 1, wherein the method comprises: The concentration of KHCO3 solution in step 5 is 0.1 mol / L.
